2010
DOI: 10.5194/bg-7-395-2010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple environmental factors on CO<sub>2</sub> emission and CH<sub>4</sub> uptake from old-growth forest soils

Abstract: Abstract. To assess contribution of multiple environmental factors to carbon exchanges between the atmosphere and forest soils, four old-growth forests referred to as boreal coniferous forest, temperate needle-broadleaved mixed forest, subtropical evergreen broadleaved forest and tropical monsoon rain forest were selected along eastern China. In each old-growth forest, soil CO 2 and CH 4 fluxes were measured from 2003 to 2005 applying the static opaque chamber and gas chromatography technique. Soil temperature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 84 publications
3
22
0
1
Order By: Relevance
“…Tests for CH 4 fluxes in upland forest soils were previously conducted with periodic (e.g., monthly) measurements taken by static chambers (Fang et al, 2010;Morishita et al, 2004). Continuous measurements have often been conducted in wetland ecosystems (e.g., Lai et al, 2012), but have rarely been used for upland soils, except for limited studies: temperate forests (Wu et al, 2011;Savage et al, 2014), tropical forest soils (Werner et al, 2006(Werner et al, , 2007Kiese et al, 2003), and agricultural fields (Yao et al, 2009).…”
Section: Implications and Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tests for CH 4 fluxes in upland forest soils were previously conducted with periodic (e.g., monthly) measurements taken by static chambers (Fang et al, 2010;Morishita et al, 2004). Continuous measurements have often been conducted in wetland ecosystems (e.g., Lai et al, 2012), but have rarely been used for upland soils, except for limited studies: temperate forests (Wu et al, 2011;Savage et al, 2014), tropical forest soils (Werner et al, 2006(Werner et al, , 2007Kiese et al, 2003), and agricultural fields (Yao et al, 2009).…”
Section: Implications and Limitationmentioning
confidence: 99%
“…Previously, CH 4 fluxes in upland forests were quantified by periodic measurements using static closed chambers (Fang et al, 2010;Itoh et al, 2009;Morishita et al, 2004Morishita et al, , 2007Smith et al, 2000). This method successfully showed spatial and temporal variations in CH 4 fluxes; at the same time, several problems were noted (Davidson et al, 2002;Norman et al, 1997;Rochette and Hutchinson, 2005;Pumpanen et al, 2004;Pihlatie et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…As an indicator of soil aeration and a regulator of gas diffusion in soil media, soil moisture or water-filled pore space (WFPS) was often found negatively correlated with CH 4 uptake in tropical forests and plantations (Butterbach-Bahl et al, 2004;Fang et al, 2010;Gütlein, Gerschlauer, Kikoti, & Kiese, 2018;Werner et al, 2006). Soil texture is a key factor, important not only for gas transport but also in controlling the microenvironment, affecting microbial CH 4 production and oxidation (Ishizuka, Tsuruta, & Murdiyarso, 2002;Le Mer & Roger, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate the impact of forest-to-rubber conversion on ecological (including control on soil CH 4 fluxes) and socioeconomic sustainability, the complex interactions between affected driving factors need to be clarified. Land-use change also affects C and N cycling, but research done so far interpreted the correlation or univariate regression between CH 4 fluxes and soil nitrogen (Dobbie & Smith, 1996;Fang et al, 2010;Veldkamp et al, 2013) without considering the fact that mineral nitrogen content and status were not independent from soil water dynamics (Bodelier, 2011). Another unsolved problem is interaction of intrinsic soil properties and changed land cover types.…”
Section: Introductionmentioning
confidence: 99%
“…High temperature helps ammonium to volatile to become ammonia entering the atmosphere, and accelerates the process of N-cycling, including the rates of mineralization, nitrification and loss as gaseous or leaching [15]. The research in the subtropical forest ecosystem showed that nitrification accounted for close to 80% of the net mineralization, and where nitrate was the main N source [16]. Precipitation enhances the loss of soil inorganic N via leaching [17,18].…”
Section: Introductionmentioning
confidence: 99%